Pemanfaatan Sumber Daya Alam Kabupaten Lebong: Sumber Daya Pangan Rebung Bambu sebagai Bahan Baku Utama Pembuatan Lemea (Makanan Tradisional Kabupaten Lebong) - Roleka Julia Marcellina; Henny Johan; Ayu Shinka Permata Sari; Adzan Akhmad Nazari; Ikmi Marlina; Tiyya Susanti Jumaitul Waini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aimed to determine the use of natural resources as food in Lebong Regency which can later be used as a learning resource for students in science learning. This research uses a survey method conducted in Lebong Regency, Bengkulu Province. The data collection technique used was interviews with the people of Lebong Regency and the Central Statistics Agency (BPS) of Lebong Regency regarding natural resources and their use. Data obtained from interviews were analyzed descriptively. The results of the research show that the people of Lebong Regency utilize natural resources, namely bamboo which is used as the main raw material in making lemea (a traditional food of the Rejang Tribe in Lebong Regency). The bamboo used in the process of making Lemea is a type of ship bamboo. The part of bamboo used in the process of making Lemea is bamboo shoots (young bamboo shoots). Lemea is a typical food of the Rejang tribe in Bengkulu Province where the main ingredient of lemea is chopped fermented bamboo shoots (young bamboo). The ingredients for the lemea mixture vary from region to region, some use river fish, red chilies, bay leaves and lemongrass. The science content that students can learn in this Lemea product is fermentation in biotechnology material. Keywords: Bamboo, Lebong, Lemea, Bamboo Shoots, Natural Resources